2016
DOI: 10.1080/08897077.2015.1015703
|View full text |Cite
|
Sign up to set email alerts
|

Screening, Brief Intervention, and Referral to Treatment for Adolescents: Attitudes, Perceptions, and Practice of New York School-Based Health Center Providers

Abstract: Findings from this study identify an important gap between an evidence-based SBIRT model and its adoption into practice within SBHCs, indicating a need for dissemination strategies targeting role responsibility, self-efficacy, and clinicians' perceptions of SBIRT effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 36 publications
4
56
0
Order By: Relevance
“…Clinicians who do intervene do not provide services on a regular basis. 20 Studies of pediatricians in other practice settings have come to similar conclusions. 10,[21][22][23] This study is the first of its kind to identify SBHC providers' perceived barriers to addressing substance use.…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…Clinicians who do intervene do not provide services on a regular basis. 20 Studies of pediatricians in other practice settings have come to similar conclusions. 10,[21][22][23] This study is the first of its kind to identify SBHC providers' perceived barriers to addressing substance use.…”
mentioning
confidence: 58%
“…Similarly, other research conducted by the authors of this paper found strong perceived role responsibility for addressing substance use among SBHC program directors and clinicians (88-97% depending on type of service). 20 In contrast, most pediatricians in other practice settings (79%) and almost half of secondary school teachers (43%) did not feel their settings were responsible for intervention and management of student substance use 11,25 which implies that SBHC staff may be more favorable and willing to deliver substance use services in their SBHCs.…”
Section: 9mentioning
confidence: 90%
See 2 more Smart Citations
“…While the resources needed to implement SBIRT in school settings and provide developmentally appropriate prevention or intervention services are substantial, mitigation of the existing school‐to‐prison pipeline is a critical social justice issue . Additional implementation research in school contexts on SBIRT protocols for adolescents will help us to understand better existing barriers to acceptance in schools, as well as the factors related to program feasibility and sustainability …”
Section: School‐based Evaluation Of the Niaaa Brief Alcohol Use Screenermentioning
confidence: 99%